Eksploitasi Foto Pribadi dalam Stiker WhatsApp: Perspektif Undang-Undang Perlindungan Data Pribadi (LEGAL DIALOGICA, 2026)
Abstract: This research aims to understand and analyze the legal regulations regarding the use of other people's personal photos as WhatsApp stickers without permission in the Personal Data Protection Law. And knowing and analyzing the form of criminal and civil sanctions against perpetrators who use other people's personal photos into WhatsApp stickers without permission. This research is a type of normative legal research that is legal research that is carried out by researching literature materials or legal materials by taking issues from law as a norm system used, normative legal research makes the norm system the center of study. The results of the study show that the legal regulation regarding the use of other people's personal photos as WhatsApp stickers without permission in the personal data protection law, is a form of personal data processing according to Law No. 27 of 2022 concerning Personal Data Protection. Photos that can identify a person include personal data, so any acquisition, alteration, storage and dissemination of photos must be based on the lawful consent of the data subject. As well as criminal and civil sanctions against perpetrators who use other people's personal photos into WhatsApp stickers without permission. Criminally, the perpetrator has the potential to be charged with the PDP Law, the Criminal Code, and the ITE Law if it causes insult, defamation, or loss to the victim. Civilly, the victim has the right to demand compensation and request the removal of the sticker and the cessation of the distribution. So, this action is not just a joke, but has real legal consequences.Abstrak:  Penelitian ini bertujuan Untuk Memahamai dan Menganalisis pengaturan hukum mengenai penggunaan foto pribadi orang lain sebagai stiker WhatsApp tanpa izin dalam Undang-Undang Perlindungan Data Pribadi. Dan  mengetahui dan menganalisis bentuk sanksi pidana dan perdata terhadap pelaku yang memanfaatkan foto pribadi orang lain menjadi stiker WhatsApp tanpa izin. Penelitian ini ialah jenis penelitian hukum normatif merupakan penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka atau Bahan Hukum dengan mengambil isu dari hukum sebagai sistem norma yang digunakan maka penelitian hukum normatif menjadikan sistem norma sebagai pusat kajian. Hasil penelitian menunjukan bahwa Pengaturan hukum mengenai penggunaan foto pribadi orang lain sebagai stiker whatsapp tanpa izin dalam undang-undang perlindungan data pribadi, merupakan bentuk pemrosesan data pribadi menurut UU No. 27 Tahun 2022 tentang Perlindungan Data Pribadi. Foto yang dapat mengidentifikasi seseorang termasuk data pribadi, sehingga setiap perolehan, perubahan, penyimpanan, dan penyebarluasan foto wajib didasarkan pada persetujuan yang sah dari subjek data. Serta Sanksi pidana dan perdata terhadap pelaku yang memanfaatkan foto pribadi orang lain menjadi stiker WhatsApp tanpa izin. Secara pidana, pelaku berpotensi dijerat UU PDP, KUHP, dan UU ITE jika menimbulkan penghinaan, pencemaran nama baik, atau kerugian bagi korban. Secara perdata, korban berhak menuntut ganti rugi serta meminta penghapusan stiker dan penghentian penyebaran. Jadi, tindakan ini bukan sekadar candaan, tetapi memiliki konsekuensi hukum yang nyata.